x+y=-3 y+z=2 x+z=7
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:03:53
x+y=-3y+z=2x+z=7x+y=-3y+z=2x+z=7x+y=-3y+z=2x+z=7x+y=-31y+z=22x+z=733-2:x-y=541+4:2x=2x=1y=-4z=6
x+y=-3 y+z=2 x+z=7
x+y=-3 y+z=2 x+z=7
x+y=-3 y+z=2 x+z=7
x+y=-3 1
y+z=2 2
x+z=7 3
3-2:x-y=5 4
1+4:2x=2
x=1
y=-4
z=6
已知(x+y)(x+z)=x,(y+z)(y+x)=2y,(z+x)(z+y)=3z,求x,y,z
试证明(x+y-2z)+(y+z-2x)+(z+x-2y)=3(x+y-2z)(y+z-2x)(z+x-2y)
x+y-z=3 y+z-x=5 z+x-y=7 求x,y,z
证明 :x/(y+z)+y/(z+x)+z/(x+y)>=3/2其中 x,y,z>0
{x+y+z=1;x+3y+7z=-1;z+5y+8z=-2
x+y+z=14 7z=x+y+2 x+z=y
(x+y-z)(x-y+z)=
x+y/2=z+x/3=y+z/4 x+y+z=27
若x+y+z=3y=2z,则x/x+y+z=?
x/2=y/3=z/5 x+3y-z/x-3y+z
x+2y=3x+2z=4y+z 求x:y:z
fangchengzu:X+Z=Y 7Z=X+Y+Z X+Y+Z=14
用行列式的性质证明:y+z z+x x+y x y z x+y y+z z+x =2 z x y z+x x+y y+z y z x 这个怎么证?
(x-2y+z)(x+y-2z)分之(y-x)(z-x) + (x+y-2z)(y+z-2x)分之(z-y)(x-y) + (y+z-2z)(x-2y+z)分之(x-z)(y-z)=?第三部分那个是 (y+z-2x)(x-2y+z)分之(x-z)(y-z)
若X:Y:Z=5:6:7那么(Y-X):(Y+Z)和(X+2Y+3Z):(3X+2Y+Z)
已知实数x y z满足x/(x+1)=y/(y+2)=z/(z+3)=(x+y+z)/3,求x+y+z的值
已知实数x y z满足x/(x+1)=y/(y+2)=z/(z+3)=(x+y+z)/3,求x+y+z的值
已知x-y/x+y=y+z/2(y-z)=z+x/3(z-x),求证8x+9y+5z=0THX..